1997
DOI: 10.1063/1.366146
|View full text |Cite
|
Sign up to set email alerts
|

Sr 2 SbMnO 6 : A new semiconductor ferroelectric

Abstract: Sr 2 SbMnO 6 is predicted to be ferroelectric with Curie temperature Tc=450(175) K on the basis of a 1990 structure determination. Calorimetry reveals a stepwise heat capacity change at Tc=431(5) K, indicative of a phase transition close to first order. A further small calorimetric anomaly occurs reproducibly at 743(10) K, consistent with an earlier report of a higher-temperature phase transition to cubic symmetry. The dielectric permittivity ε′ increases sharply at Tc=466(10)K in the range 0.1–100 kHz; ε′ ris… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2004
2004
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 10 publications
0
9
0
Order By: Relevance
“…[55], but has a nonpolar structure, as reported in subsequent papers for both disordered and partially ordered cases. This negative result, though disappointing when considered in the framework of the discovery of new ferroelectric materials, does illustrate the value of including first principles results in evaluating structural data.…”
Section: Survey Of Known Polar Systemsmentioning
confidence: 58%
See 3 more Smart Citations
“…[55], but has a nonpolar structure, as reported in subsequent papers for both disordered and partially ordered cases. This negative result, though disappointing when considered in the framework of the discovery of new ferroelectric materials, does illustrate the value of including first principles results in evaluating structural data.…”
Section: Survey Of Known Polar Systemsmentioning
confidence: 58%
“…A value for the band gap of 0.50(2) eV was extracted from the Arrhenius behavior of the conductivity in Ref. [55] (in which the space group was reported to be polar I4mm, consistent with Ref. [56]).…”
Section: Survey Of Known Polar Systemsmentioning
confidence: 76%
See 2 more Smart Citations
“…The Sr 2 MnSbO 6 perovskite is one compound of this type, and it has been synthetized via molten salt synthesis (MSS) method and convectional solid-state methods for example by (Cheah et al, 2006;Ivanov et al, 2009;Parada et al, 2018;Preethi-Meher et al, 2012). Experimental studies of Sr 2 MnSbO 6 have shown that this compound presents ferroelectric and ferromagnetic behavior in the I4m, I4mm, I4mcm phases, as well as it exhibits high dielectric constant in the cubic phase Fm-3m (Antara, et al, 2011;Foster, et al,1997;Majhi & Varma, 2007). Modifications of this compound recently have been reported by (Bazuev et al, 2021), where is studied the effect of substitutions on the phase formation, structure and magnetic properties of the Sr 2 MnSbO 6 compound.…”
Section: Physical Sciencesmentioning
confidence: 99%